1997
DOI: 10.1111/j.1365-2249.1997.273-ce1163.x
|View full text |Cite
|
Sign up to set email alerts
|

Wild isolates of Plasmodium falciparum malaria show decreased sensitivity to in vitro inhibition of parasite growth mediated by autologous host antibodies

Abstract: SUMMARYAntigenic diversity in field populations of Plasmodium falciparum parasites may delay the acquisition of protective immunity to malaria, the development of which may thus require repeated exposure to infection over a prolonged period of time. In this study we show that P. falciparum parasites may vary in their sensitivity to antibody-mediated invasion/growth inhibition in vitro. Wild isolates of P. falciparum from children living in an endemic area of Burkina Faso were tested for their sensitivity to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…Two major invasion pathways have been described in P. falciparum : a sialic acid dependent (W2Mef) pathway and a sialic acid independent (3D7 and D10) pathway (Duraisingh et al, 2003; Ord et al, 2012). The different growth inhibition levels among our laboratory strains may be secondary to parasite antigenic diversity and pathways involved in merozoite invasion as reported by others (Dent et al, 2008; McCallum et al, 2008; Mu et al, 2007; Wahlin Flyg et al, 1997). Using three different laboratory strains with varying invasion pathways in the assay strengthens the validity of our results.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Two major invasion pathways have been described in P. falciparum : a sialic acid dependent (W2Mef) pathway and a sialic acid independent (3D7 and D10) pathway (Duraisingh et al, 2003; Ord et al, 2012). The different growth inhibition levels among our laboratory strains may be secondary to parasite antigenic diversity and pathways involved in merozoite invasion as reported by others (Dent et al, 2008; McCallum et al, 2008; Mu et al, 2007; Wahlin Flyg et al, 1997). Using three different laboratory strains with varying invasion pathways in the assay strengthens the validity of our results.…”
Section: Discussionsupporting
confidence: 66%
“…However, the trend of decreasing levels with time is apparent; 3) as this cohort experienced very few clinical malaria infections by 12 months of age, we were unable to correlate GIA levels with potential protection from disease; 4) using only one Pf field isolate for GIA which may not truly represent the antigenic diversity of the parasite population found in this as has been demonstrated by others (Wahlin Flyg et al, 1997); and 5) not examining the GIA levels in maternal blood.…”
Section: Discussionmentioning
confidence: 79%
“…In this study, we have provided the first evidence that opsonic phagocytosis of P. falciparum merozoites is a robust correlate of acquired immunity using both laboratory parasite strains and plasma-matched isolates adapted from the field. Both growth inhibition and trophozoite functional antibodies have been shown to be largely strain specific (15)(16)(17)(18)(19), which limits their utility for assessing immunity in areas of endemicity with diverse parasite populations. In this study, high levels of opsonizing antibodies against all strains were associated with an 85% decrease in the risk of clinical malaria in individuals uninfected at baseline.…”
Section: Discussionmentioning
confidence: 99%
“…FMP2.1/ AS02A and combination B vaccines that consist of a single allelic sequence of AMA-1 and MSP2, respectively, showed only partial protective efficacy that was restricted to infections with P. falciparum that expressed vaccine-like alleles (13,14). Growth-inhibitory and trophozoite-agglutinating antibodies are acquired in a strain-specific manner (15)(16)(17)(18)(19); however, the impact of parasite diversity on opsonization remains unknown. More generally, it is unclear to what extent malaria immunity results from the accumulation of a broad repertoire of uniquely specific antibodies or from a narrow repertoire against conserved antigens.…”
mentioning
confidence: 99%
“…In a study performed in Burkina Faso, we observed that P. falciparum parasites may vary in their sensitivity to antibody-mediated invasion/growth inhibition in vitro, indicating a diversity in the target antigens [60]. Field isolates of P. falciparum from asymptomatic children were also tested for their sensitivity to the growth-inhibitory effects of antibodies originating from the same (homologous) or from other donors (heterologous) [36]. A signi®cantly lower invasion-inhibition activity was obtained when the isolates and antibodies were tested in homologous combinations compared to heterologous combinations.…”
Section: Effects Of Immune Pressure On Parasites and Their Susceptibimentioning
confidence: 99%